Performance of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) Strains on Eggs from Different Populations of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Alessandro Bandeira Dalbianco; Diego Fernando Daniel; Dirceu Pratissoli; Daniel de Lima Alvarez; Nadja Nara Pereira da Silva; Daniel Mariano Santos; Santino Seabra Júnior; Regiane Cristina de Oliveira (Agronomy, 2025)
Tomato is the most widely cultivated fruit–vegetable worldwide, and the tomato leafminer (Tuta absoluta) is the primary pest of this crop. In this context, biological control using parasitoids belonging to the genus Trichogramma is crucial. This study aimed to evaluate the biological characteristics of T. pretiosum strains collected from different locations and exposed to eggs from various T. absoluta populations/generations, using parameters such as parasitism capacity, viability (percentage of emergence), sex ratio, and female longevity. The presence of endosymbionts in the T. absoluta populations was also assessed. The experiment followed a randomized design, with treatments consisting of eggs from T. absoluta populations collected in different years (2019, 2020, 2021, 2022, and 2023) and different strains of T. pretiosum. We used 20 replicates, with one female per replicate in each treatment, organized in a 5 × 4 factorial scheme (five populations of T. absoluta × four strains of T. pretiosum). The S2 strain of T. pretiosum was found to be the most efficient in terms of biological characteristics for parasitism of T. absoluta eggs, especially in T. absoluta populations collected in recent years (2022 and 2023). These results suggest that S2 is the preferred strain for future studies aimed at using this parasitoid as a control agent to combat T. absoluta. The endosymbionts Arsenophonus and Serratia were identified in T. absoluta populations collected in 2019–2020 and 2020–2021, respectively. These findings highlight the presence of these microorganisms in pest populations in different years.